The systolic blood pressure difference between arms and cardiovascular disease in the Framingham Heart Study - Weinberg, Ido; Gona, Philimon; O'Donnell, Christopher J; Jaff, Michael R; Murabito, Joanne M (The American journal of medicine, 2014)
An increased interarm systolic blood pressure difference is an easily determined physical examination finding. The relationship between interarm systolic blood pressure difference and risk of future cardiovascular disease is uncertain. We described the prevalence and risk factor correlates of interarm systolic blood pressure difference in the Framingham Heart Study (FHS) original and offspring cohorts and examined the association between interarm systolic blood pressure difference and incident cardiovascular disease and all-cause mortality. An increased interarm systolic blood pressure difference was defined as ≥ 10 mm Hg using the average of initial and repeat blood pressure measurements obtained in both arms. Participants were followed through 2010 for incident cardiovascular disease events. Multivariable Cox proportional hazards regression analyses were performed to investigate the effect of interarm systolic blood pressure difference on incident cardiovascular disease. We examined 3390 (56.3% female) participants aged 40 years and older, free of cardiovascular disease at baseline, mean age of 61.1 years, who attended a FHS examination between 1991 and 1994 (original cohort) and from 1995 to 1998 (offspring cohort). The mean absolute interarm systolic blood pressure difference was 4.6 mm Hg (range 0-78). Increased interarm systolic blood pressure difference was present in 317 (9.4%) participants. The median follow-up time was 13.3 years, during which time 598 participants (17.6%) experienced a first cardiovascular event, including 83 (26.2%) participants with interarm systolic blood pressure difference ≥ 10 mm Hg. Compared with those with normal interarm systolic blood pressure difference, participants with an elevated interarm systolic blood pressure difference were older (63.0 years vs 60.9 years), had a greater prevalence of diabetes mellitus (13.3% vs 7.5%,), higher systolic blood pressure (136.3 mm Hg vs 129.3 mm Hg), and a higher total cholesterol level (212.1 mg/dL vs 206.5 mg/dL). Interarm systolic blood pressure difference was associated with a significantly increased hazard of incident cardiovascular events in the multivariable adjusted model (hazard ratio 1.38; 95% CI, 1.09-1.75). For each 1-SD-unit increase in absolute interarm systolic blood pressure difference, the hazard ratio for incident cardiovascular events was 1.07 (95% CI, 1.00-1.14) in the fully adjusted model. There was no such association with mortality (hazard ratio 1.02; 95% CI 0.76-1.38). In this community-based cohort, an interarm systolic blood pressure difference is common and associated with a significant increased risk for future cardiovascular events, even when the absolute difference in arm systolic blood pressure is modest. These findings support research to expand clinical use of this simple measurement.